Vigeland – Municipality of Oslo: Decision of the Court of Justice of the European Free Trade Association States (EFTA Court) 6 April 2017 – Case No. E-5/16 (IIC - International Review of Intellectual Property and Competition Law, 2017)
The registration as a trade mark of a sign which consists of works for which the copyright protection period has expired, is not in itself contrary to public policy or accepted principles of morality within the meaning of Art. 3(1)(f) of Directive 2008/95/EC. Whether registration for signs that consist of works of art as a trade mark shall be refused on the basis of accepted principles of morality within the meaning of Art. 3(1)(f) of Directive 2008/95/EC depends, in particular, on the status or perception of the artwork in the relevant EEA State. The risk of misappropriation or desecration of a work may be relevant in this assessment. Registration of a sign may only be refused on basis of the public policy exception provided for in Art. 3(1)(f) of Directive 2008/95/EC, if the sign consists exclusively of a work pertaining to the public domain and registration of this sign would constitute a genuine and sufficiently serious threat to a fundamental interest of society. Article 3(1)(e)(iii) of Directive 2008/95/EC may apply to two-dimensional representations of three-dimensional shapes, including sculptures. Article 3(1)(c) of Directive 2008/95/EC must be interpreted as being applicable to two-dimensional and three-dimensional representations of the shape of a good. Article 3(1)(b) of Directive 2008/95/EC must be interpreted as meaning that where a sign is descriptive within the meaning of Art. 3(1)(c), that sign necessarily lacks distinctiveness under Art. 3(1)(b). Should the referring body find that the sign at issue is not descriptive, it may assess its distinctiveness for the purposes of Art. 3(1)(b) in relation to the goods and services covered by that mark and to the presumed expectations of an average consumer of the category of goods and services in question, who is reasonably well-informed, observant and circumspect.